The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/cells11071129
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Receptor Influences Intestinal Barriers in Health and Disease

Abstract: Vitamin D receptor (VDR) executes most of the biological functions of vitamin D. Beyond this, VDR is a transcriptional factor regulating the expression levels of many target genes, such as genes for tight junction proteins claudin-2, -5, -12, and -15. In this review, we discuss the progress of research on VDR that influences intestinal barriers in health and disease. We searched PubMed and Google Scholar using key words vitamin D, VDR, tight junctions, cancer, inflammation, and infection. We summarize the lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 176 publications
0
16
0
4
Order By: Relevance
“…In fact, approximately 3% of the mouse and human genomes are directly or indirectly regulated by vitamin D, suggesting a broad contribution of vitamin D/VDR in diverse disease mechanisms ( 43 , 44 ). For several organ dysfunctions, the vitamin D/VDR signaling pathway is essential in regulating connectivity components and maintaining epithelial barrier integrity, including intestinal inflammation, infection, and chronic inflammatory lung diseases ( 45 ). It was previously proposed that the main mechanism by which VDR activation affected autoimmunity was through genetic activation of myeloid immune cells, particularly antigen-presenting dendritic cells (DCs), thereby triggering a tolerance status in the immune system, particularly in DCs ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, approximately 3% of the mouse and human genomes are directly or indirectly regulated by vitamin D, suggesting a broad contribution of vitamin D/VDR in diverse disease mechanisms ( 43 , 44 ). For several organ dysfunctions, the vitamin D/VDR signaling pathway is essential in regulating connectivity components and maintaining epithelial barrier integrity, including intestinal inflammation, infection, and chronic inflammatory lung diseases ( 45 ). It was previously proposed that the main mechanism by which VDR activation affected autoimmunity was through genetic activation of myeloid immune cells, particularly antigen-presenting dendritic cells (DCs), thereby triggering a tolerance status in the immune system, particularly in DCs ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dysbiosis of the gut microbiome could indirectly participate in the development or progression of breast cancer via bacterial metabolites from the gut (SBA, SCFA, PAMPs, vitamin) and immune and inflammatory modulators (TLR, cytokines) that are inextricably interlinked with the microbiome from the GI tract 32 . VDR expression increases epithelial integrity and attenuates inflammation 52 . Interestingly, we found some butyrate-related modules were also Epidemiological and experimental studies have indicated a protective action of vitamin D against colorectal cancer [54][55][56][57][58][59][60] .…”
Section: Discussionmentioning
confidence: 99%
“…It also inhibits transcription of ZO-1, claudin-5, and occludin genes and increases the tight junction protein claudin-2 which enhance intestinal permeability. Thus, lacking intestinal epithelial VDR regulation in inflamed intestine leads to hyperfunction of Claudin-2 and exaggerates the inflammatory responses in the intestines [ 47 ].…”
Section: Pleiotropic Effects Of Vitamin D In Inflammatory-based Diseasesmentioning
confidence: 99%